Penerapan Model Picture And Picture dalam Meningkatkan Aktivitas dan Hasil Belajar Pembelajaran Tematik Siswa Kelas II Sekolah Dasar - Herman, Herman; Supriatna, Irfan (UNIB Press, 2020)
This study aims to improve the activities and learning outcomes of thematic learning in grade II elementary school students through the application of picture and picture models. The research method used was classroom action research (clascroom action research) with a cycle of Kemmis and Taggart using 4 stages namely planning, action, observation, reflection. Research subjects with 27 students consisting of 14 men and 13 women. The results of the study stated that an increase in student activity and learning outcomes in thematic learning in class II, this can be seen from the increase in the average acquisition of student activity scores in the first cycle obtained an average score of 31 increased to 35.5 with a good category in the second cycle. Then the learning outcomes are proven from the average value and the percentage of student learning in the form of cognitive, affective and psychomotor values. Cognitive Value The highest average value is in the natural science subjects at 84.16 with the percentage of student learning reaching 100% and the lowest average value in mathematics subjects at 80.83 with the percentage of student learning only reaching 83.39%. Affective value, the highest percentage of criteria namely in SBK, Natural Sciences and Civics reached 88.88% or as many as 24 people and the lowest percentage of criteria namely in mathematics subjects only reached 81.48% or as many as 22 people. Psychomotor scores, the highest percentage of criteria namely SBK, Natural Sciences and Civics reached 88.88% or as many as 24 people and the lowest percentage of criteria namely in Mathematics and Social Sciences subjects only reached 85.18% or as many as 23 people. The conclusion is that the application of picture and picture models in grade II elementary schools can increase the activities and learning outcomes of thematic learning.